Ballet shoes [videorecording (DVD)] - Goldbacher, Sandra; Boynton, Lucy; Watson, Emma, 1990-; Paige, Yasmin; Streatfeild, Noel (Distributed by Koch Entertainment, 2008)
Three girls adopted by an explorer are raised as sisters by his niece. As each of the girls have their own dreams, they learn that in order to realize them, they must also keep their family together.